2001
DOI: 10.1146/annurev.med.52.1.471
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Distal Renal Tubular Acidosis: New Understandings

Abstract: The primary or hereditary form of distal renal tubular acidosis (dRTA), although rare, has received increased attention recently because of dramatic advances in the understanding of its genetic basis. The final regulation of renal acid excretion is effected by various acid/base transporters localized in specialized cells in the cortical collecting and outer medullary collecting tubules. Inherited defects in two of the key acid/base transporters involved in distal acidification, as well as mutations in the cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
0
6

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 58 publications
(65 reference statements)
0
58
0
6
Order By: Relevance
“…It is tempting to speculate that this is because these mutations result in net bicarbonate secretion into the urine rather than overall functional cellular failure, but this has not been assessed. One way to address this would be to measure urine pCO 2 , predicting that in affected members of this kindred and the R901X kindred, it would not be reduced to the extent usually observed in dRTA. It is unfortunate that severe nephrocalcinosis and consequent anatomical disruption renders the interpretation of pCO 2 levels unreliable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is tempting to speculate that this is because these mutations result in net bicarbonate secretion into the urine rather than overall functional cellular failure, but this has not been assessed. One way to address this would be to measure urine pCO 2 , predicting that in affected members of this kindred and the R901X kindred, it would not be reduced to the extent usually observed in dRTA. It is unfortunate that severe nephrocalcinosis and consequent anatomical disruption renders the interpretation of pCO 2 levels unreliable.…”
Section: Discussionmentioning
confidence: 99%
“…This disorder is usually accompanied by hypokalemia, metabolic bone disease, nephrocalcinosis, and/or nephrolithiasis (1)(2)(3). Mutations in SLC4A1 (MIM 109270), encoding the polytopic chloride-bicarbonate exchanger known as AE1, have been reported as the sole genetic cause of autosomal dominant dRTA (ddRTA) (MIM #179800) (4 -9) and also rarely cause autosomal recessive dRTA (10 -14).…”
mentioning
confidence: 99%
“…BASIC RESEARCH www.jasn.org responsible for distal and type 4 RTA. [12][13][14][15][16][17] However, no previous reports have focused on the role of V1aR as a causative factor in type 4 RTA. Previously, we showed that the stimulation of V1aR in the macula densa is the first step of renin production and the deficient of V1aR in macula densa causes hyporeninemic hypoaldosteronism.…”
Section: V1armentioning
confidence: 99%
“…1,2,10,11 Thus far, many functional defects of these transporters have been hypothesized to cause distal type or type 4 renal tubular acidosis (RTA). [12][13][14][15][16][17] Type 4 RTA, which is a hyperkalemic distal RTA, is known to be caused by hyporeninemic hypoaldosteronism. 17,18 Although the treatment of patients with type 4 renal tubular acidosis by fludrocortisones has been shown to ameliorate acidosis, the precise mechanisms of type 4 RTA have been unknown.…”
mentioning
confidence: 99%
“…Primary distal RTA may be observed sporadically or with autosomal dominant or recessive transmission (20) (Tables 1 and 3). Autosomal dominant distal RTA has been found to be associated in several kindred with mutations in the gene encoding the Cl Ϫ -HCO 3 Ϫ exchanger AE1 or band 3 protein (21).…”
Section: Distal Rta (Type 1)mentioning
confidence: 99%